If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4X + -8 = 3(2X + -4) Reorder the terms: -8 + 4X = 3(2X + -4) Reorder the terms: -8 + 4X = 3(-4 + 2X) -8 + 4X = (-4 * 3 + 2X * 3) -8 + 4X = (-12 + 6X) Solving -8 + 4X = -12 + 6X Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-6X' to each side of the equation. -8 + 4X + -6X = -12 + 6X + -6X Combine like terms: 4X + -6X = -2X -8 + -2X = -12 + 6X + -6X Combine like terms: 6X + -6X = 0 -8 + -2X = -12 + 0 -8 + -2X = -12 Add '8' to each side of the equation. -8 + 8 + -2X = -12 + 8 Combine like terms: -8 + 8 = 0 0 + -2X = -12 + 8 -2X = -12 + 8 Combine like terms: -12 + 8 = -4 -2X = -4 Divide each side by '-2'. X = 2 Simplifying X = 2
| 75+2x=15 | | X+2=2overy-1 | | +t/12=-3 | | -6b+28=9b-2 | | 3x-9=4x-24 | | 3(4x+1)=3+12x-3 | | 36+2y-15=12y-9-5y | | 8-4+2R-4R+8R= | | 2L+2W=W+84 | | 8-r=3r-14 | | x-1b=72 | | .666h-9=6-.666h | | 8x+6y-10=0 | | 24b+4=52 | | (x-3)(x-4)-(x+4)=0 | | 2n^3-24n^2-23048n=0 | | 4.3+7.5=5.8 | | 10v^2=11v+6 | | -3-10=-46 | | -(12+2r)-(r+8)=-7r+3r | | 10U-2U= | | 6x^2-13x+4= | | 4.29b-0.692=11.749 | | 3[2(5x-7)-3(4x-6)]-4[5(x-1)-7x]=6[-4(x+2)+7x] | | 6+5(8w-9)= | | 36=2L+W | | 1w+5=4 | | 3-2(x-4)=2x-5 | | 3(4x+1)=3+12x-2 | | (X+10)+(4x-20)=90 | | 7R*2+8R+8R= | | 3x(.29)=3 |